Frequency of distribution and relationship of polymorphism of milk proteins in Holstein bulls with the productivity of their mothers and assessment of daughters - Ludmila I. Kuzyakina; Elena N. Usmanova; Egor A. Smirnov; Elena V. Mokerova (Аграрная наука Евро-Северо-Востока, 2025)
The kappa-casein and beta-casein genes control milk yield, quality of milk and dairy products, therefore they represent important breeding criteria for dairy cattle breeds. The frequency of occurrence of different kappa- and beta-casein genotypes was studied in 68 Holstein bulls of imported and domestic breeding owned by Kirovplem JSC of the Kirov region, data on the milk productivity of their mothers and the results of the evaluation of their daughters were analyzed. It was found that among the analyzed bulls for kappa casein, the AA genotype prevailed - 50.0 % of producers. The AB and BB genotypes were found in 30.9 and 19.1 % of bulls, respectively. The highest productivity according to yield, fat content and protein content in milk (14,573 kg, 4.39 and 3.47 %, respectively) was obtained from mothers of bulls with the AB genotype, while their superiority in milk yield and protein content was statistically significant compared to mothers of bulls with the AA genotype. Relative to their peers, the daughters of bulls with the AB genotype were also more productive, their weight gain was 720 kg, 0.21 %, 0.12 %, which was significantly higher in fat and protein content in milk compared to the AA genotype. Beta-casein was dominated by bulls with the A1A2 genotype (51.5 %). There were fewer producers with the A1A1 and A2A2 genotypes, respectively – 27.9 and 20.6 %. The highest milk yield was found in mothers of bulls with the beta-casein A2A2 genotype – 14482 kg. Significantly higher fat content – 4.49 % in mothers of bulls with the A1A2 genotype. Mothers of bulls with casein A1A1 and A1A2 also have significantly higher milk protein content (3.43 and 3.41 %). A comparison of daughters with their peers showed that the greatest increase in milk yield was given to daughters from bulls with genotypes A2A2 – 745 kg and A1A2 – 717 kg, which was statistically significant, in mass fraction of fat – daughters of bulls with genotype A1A2 – 0.17 %, and in protein – with genotype A2A2 – 0.11 %. To increase milk productivity and improve the quality of milk in the average herd, the number of animals from bulls with these kappa- and beta-casein genotypes should be increased.